Association between patient activation, self-management behaviours and clinical outcomes in adults with type 2 diabetes: a systematic review with narrative synthesis - Simon J Griffin; Julia Mueller; Rebecca Richards; Amy Ahern; Jack M Birch; Robert S Beckett; Koghanadhacharve Thinakaran; Sara F Shaida; Harriet M Wills (BMJ Open)
Objectives Patient activation (PAct)—a measure assessing an individual’s perceived knowledge, skills and confidence in managing their health and well-being—is often used to personalise and evaluate care, although its causal link to self-management behaviours (SMBs) and clinical outcomes remains uncertain. We aimed to synthesise the evidence on the causal association between PAct, SMBs and clinical outcomes in type 2 diabetes (T2D).Design Systematic review and narrative synthesis of data summarised in a harvest plot.Data sources We searched Medline, Embase, CENTRAL, PsycInfo, Web of Science and CINAHL up to April 2024 for relevant English articles.Eligibility criteria We included studies of any quantitative design that reported on the association of PAct with clinical outcomes or SMBs in adult patients with T2D.Data extraction and synthesis Two independent reviewers were involved, and any disagreements were discussed and resolved collaboratively. Risk-of-bias (RoB) was assessed using an adapted RoB Assessment Tool for Nonrandomised Studies. Levels of evidence were evaluated for each T2D-related outcome.Results We identified 21 studies published between 2009 and 2023, including 15 cross-sectional studies and no randomised controlled trials. Eleven studies were conducted in the USA. Seventeen studies used the Patient Activation Measure questionnaire. There is moderate evidence that higher PAct scores are associated with better glycated haemoglobin levels (studies reporting on this association, n=14). There is very limited evidence that PAct improves diet (n=5) and physical activity (n=6). All other clinical outcomes and SMBs had inconclusive results due to either inconsistent or insufficient evidence, or both.Conclusion A causal relationship between PAct, clinical outcomes and SMBs in T2D cannot be established due to inconsistent evidence and a lack of high-quality studies. Thus, the use of PAct scores as a tailoring tool and an outcome measure in healthcare services requires further evaluation.PROSPERO registration number CRD42021230727.